AB0291 Therapy response in rheumatoid arthritis patients and concomitant fibromyalgia. (23rd January 2014) - Cojocaru-Gofita, I.; Ciurea, P.; Rosu, A.; Musetescu, A.; Vreju, F.; Florea, M.; Barbulescu, A.; Hoanca, C.
Abstract : Background: It has been stated that rheumatoid arthritis (RA) and fibromyalgia (FM) can simultaneously affect patients. At the same time DAS28 values tend to be higher in RA patients whom have also developed FM and this might cause a more aggressive therapeutic approach and further misinterpretation of the clinical outcome in this group of patients. Objectives: To study the effect and beneficial outcome of remissive therapy in a Romanian RA cohort diagnosed with concomitant FM Methods: The initial group included 34 established RA female patients with a disease duration of minimum 12 months (diagnosed between 2006-2008) and a mean age of 41.3±4 years which were also diagnosed with FM within 3 to 6 months prior to inclusion. A second group consisting of 20 RA female patients with no clinical signs of FM was chosen as controls. All patients were started on a stable Methotrexate dose of 7.5-15mg/week for the first 12 weeks. Both groups were evaluated every 3 to 6 months between 2009-2011 through the Disease Activity Score on 28 joints (DAS284v) Results: The first group showed little if no DAS28 improvement with a mean value of 5.1±0.7 (p<0.001) after 3 months of MTX therapy leading towards dosage increasing while the controls showed a mean value of 4.2±0.5 (p<0.001) thus avoiding dosage adjustments. After the second evaluation point at 6 months, 7 out of the initial 34 patients included in the study group needed a higher MTX dosage showing a mean value of DAS28 of 4.5. After the first 12 months 11 patients from the study group and 3 controls were administered a different remissive therapeutic agent due to their disease activity score – a mean value of DAS28 of 4.8±0.7 (p<0.001) Conclusions: In the analyzed groups fibromyalgia showed itself to be an aggravating factor adding to the rheumatoid arthritis. Furthermore patients diagnosed with both RA and FM needed a more aggressive change in their treatment regimen showing that an extremely careful approach is needed in the RA cases where a concomitant FM may develop simultaneously Disclosure of Interest: None Declared